Penyidikan Tindak Pidana Kekerasan Dalam Rumah Tangga Yang Dilakukan Oleh Suami Terhadap Istri Di Wilayah Hukum Polresta Padang Studi Kasus: Lp/601/Ix/2023/Spkt/Polresta Padang ) - Nurlinda yenti; Rahmatul Fajri Putri (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
Article 1 of Law Number 23 of 2004 concerning the elimination of domestic violence, states that every act against someone, especially women, which results in physical, sexual misery and/or domestic neglect, including threats to commit acts, or deprivation of liberty is against the law in household sphere. The formulation of the problem in this research is: How is the investigation of criminal acts of domestic violence at Padang Police: LP/B/601/IX/2023 SPKT/Padang Police? . What are the obstacles in investigating criminal acts of domestic violence at the Padang Police LP/B/601/IX/2023 SPKT/Padang Police? How are efforts to overcome obstacles in investigating criminal acts of domestic violence LP/B/601/IX/2023/SPKT Padang Police? The problem approach used is a sociological juridical approach, namely looking at the facts in the field and linking them to applicable law. The results of this research are the implementation of investigations into criminal acts of domestic violence committed by husbands against wives in the jurisdiction of the Padang Police LP/B/601/IX/2023/SPKT Padang Police). The results of the research were a report from the victim to the PPA Unit of the Padang Police, after which the police carried out an investigation by investigators, then continued with the investigation, after finding the perpetrator the investigators made an arrest, then investigators carried out a search, confiscation and detention at the Padang Police for 20 days from 11 September to 01 October 2023, then investigators carried out examinations of the suspects until the case files were handed over to the prosecutor's office. Obstacles in investigating criminal acts of domestic violence committed by husbands against wives in the jurisdiction of Padang Police LP/B/601/IX/2023/ SPKT/ Padang Police) are the lack of competent investigation personnel in the PPA Unit, not having a safe house for victim. The effort to overcome obstacles in investigating criminal acts of domestic violence committed by husbands against wives in the jurisdiction of the Padang Police LP/B/601/IX/2023/SPKT Padang Police) is to propose additional personnel, entrusting them to the victim's parents' house.